Chitosan/graphene oxide‐based multifunctional pH‐responsive hydrogel with significant mechanical strength, self‐healing property, and shape memory effect - Nath, Jayashree; Chowdhury, Anupam; Dolui, Swapan Kumar (Advances in polymer technology, 2018)
Synthesis of hydrogel with multifunctional properties still remains a challenge within the scientific community. Hydrogels having stimulus‐responsive properties are a few of the desired properties for real‐life applications. This work highlights the synthesis of multifunctional pH‐sensitive hydrogels, based on chitosan (CS) and graphene oxide (GO), via physical cross‐linking. The properties of hydrogels were optimized using various characterization techniques. Successful GO incorporation into the CS matrix was clearly confirmed by Fourier transform infrared analysis. Scanning electron microscope and TEM micrographs portray rough and porous surface morphology of the composite hydrogels. The prepared hydrogels have demonstrated enhanced thermal properties due to the incorporation of GO. To investigate the pH‐responsive behavior, the pH‐dependent study for the hydrogels was carried out in acidic and basic media. Increasing the amount of GO content inside the gel imparted enhanced mechanical properties to the hydrogel. There was a sharp increase in tensile strength from 4.37 to 20.96 MPa accompanied by an increase in Young's modulus from 0.122 to 0.364 MPa. DMA confirmed better elastic behavior of the composite hydrogel. The hydrogel exhibited fast self‐healing property when cleaved under ambient conditions. In addition, the hydrogel also exhibited a shape memory effect both in the alcoholic solution and in the solution of metal cation. A multifunctional pH‐responsive hydrogel based on Chitosan and Graphene Oxide has been synthesized which exhibits several times higher mechanical strength, self‐healing properties and shape memory effect in comparison to the pristine Chitosan hydrogel.